THE INFLUENCE OF FOOD SANITATION HYGIENE PERCEPTION ON PURCHASING DECISIONS OF STREET VENDORS IN THE HOTEL X AREA, JAKARTA - Risdi, Ardila; Nugraheni, Prastiti Laras; Irwanto, Reno (Jurnal Gizi dan Pangan Soedirman, 2025)
Perception of food hygiene and sanitation is one of the essential factors influencing consumers' purchasing decisions toward street food. This study aims to determine the influence of food hygiene and sanitation perception on purchasing decisions among street food vendors located behind a five-star hotel in Jakarta. This research employed a quantitative approach using incidental sampling techniques. The respondents were 100 five-star hotel employees who frequently purchased street food around Hotel X. The research instrument used a Guttman scale questionnaire tested for validity and reliability. The data were analyzed using simple linear regression. The results showed a positive and significant influence between the perception of food hygiene and sanitation and purchasing decisions, with a significance value of 0.001 < 0.05 and an R square value of 0.111. This indicates that 11.1% of the variation in purchasing decisions can be explained by perceptions of hygiene and sanitation. It can be concluded that the better the consumers' perception of the hygiene and sanitation practices of street food vendors, the greater their tendency to make a purchase.